Nutritional Content and Bioactive Compounds of Banana Peel and Its Potential Utilization: A Review - Nur Anis Insyirah Muhammad Ansari; Nur Zazarina Ramly; Nur Huda Faujan; Norlelawati Arifin (USIM Press, 2024)
VOL. 9 NO. 1 (2023) Page (74-86)